The in-session discourse of unresolved/disorganized psychotherapy patients: an exploratory study of an attachment classification - Talia, Alessandro; Taubner, Svenja; Miller-Bottome, Madeleine; Muurholm, Signe Dall; Winther, Anna; Frandsen, Frederik Weischer; Harpøth, Tine; Onofri, Antonio; Kongerslev, Mickey T.; Simonsen, Sebastian; Poulsen, Stig; Duschinsky, Robbie (Frontiers in psychology, 2022)
The Unresolved/disorganized (U/d) attachment classification has generated considerable interest among clinicians. This is in part based on its empirical associations with adult mental health, parenting practices, and treatment outcomes. Despite decades of theorizing, however, we have little empirical information regarding how patients with a U/d classification assigned by accredited coders actually behave or speak in psychotherapy sessions. Here, we take a step towards bridging this gap by reporting our observations of the psychotherapy session transcripts of 40 outpatients who were independently classified as U/d on the Adult Attachment Interview (AAI), the gold standard measure of adult attachment research. These patients were extracted from a larger sample of 181 and compared to others without a U/d classification. In this paper, we discuss two different discourse styles associated with a U/d classification. Some U/d patients did not seem to sufficiently elicit the therapist’s endorsement of what they said. For example, they did not justify their claims with examples or explanations, or did not consider others’ intentions or experiences. Other U/d patients were credible, but left the listener uncertain as to the underlying point of their discourse, for example, by glaringly omitting the consequences of their experiences, or interrupting their narratives mid-way. In the discussion, we place these observations in the context of recent thinking on attachment and epistemic trust, and discuss how this study may form the basis for future quantitative studies of psychotherapy.